Controle da frota automotiva do poder judiciário através da internet das coisas - Stroligo, Gabriel Wermuth (Universidade Federal do Tocantins, 2021)
The concept of resource optimization is widely used in technology sectors, mainly with regard to software development. However, the application of such optimizations has advanced to several other areas. The main example are companies, both public and private, that optimize from human resources, going through the control of a company's costs until the potential use of tools necessary for the business operation. In this way, the use of Internet of Things has largely helped to reduce waste, with the use of sensors capable of transforming into precise numbers something that in most cases was estimated erroneously. Vehicles continue to be one of the main tools used by various branches of business and contribute to being a major source of costs. Thus, facing the profound transformations that are taking place in the economic, social and environmental scenario in Brazil, and which are reflecting in a significant way in the current public management practices, there is an increasing need for a contribution so that such regulations have an assertive technical background on the use of the automotive fleet of the Judicial Branch of the State of Tocantins to conduct its processes and procedures in an efficient and appropriate manner. Thus, an embedded system capable of obtaining vehicle data through the CAN protocol and sent to a NoSQL database through GPRS is developed and tested serving as a basis for further development of a fleet management system. For validation purposes the system was tested in real time on a moving vehicle.